Functional analysis of problem behavior: A 40‐year review - Melanson, Isaac J.; Fahmie, Tara A. (Journal of applied behavior analysis, 2023)
Extensive reviews of functional analysis literature were conducted 10 (Beavers et al., 2013) and 20 (Hanley et al., 2003) years ago; we expanded this review to capture the vast and innovative functional analysis research that has occurred over the past decade. Our review produced 1,333 functional analysis outcomes from 326 studies on the functional analysis of problem behavior between June 2012 and May 2022. Some characteristics of functional analysis studies were similar across the current and previous two reviews (e.g., child participants, developmental disability diagnosis, use of line graphs depicting session means, differentiated response outcomes). Other characteristics deviated from the previous two reviews (e.g., increase in autistic representation, outpatient settings, use of supplementary assessments, the inclusion of tangible conditions, and multiple function outcomes; decrease in session durations). We update previously reported participant and methodological characteristics, summarize outcomes, comment on recent trends, and propose future directions in the functional analysis literature.